Image‐defined risk factors in unresectable neuroblastoma: SIOPEN study on incidence, chemotherapy‐induced variation, and impact on surgical outcomes. Issue 11 (25th April 2017) - Avanzini, Stefano; Pio, Luca; Erminio, Giovanni; Granata, Claudio; Holmes, Keith; Gambart, Marion; Buffa, Piero; Castel, Victoria; Valteau Couanet, Dominique; Garaventa, Alberto; Pistorio, Angela; Cecchetto, Giovanni; et al.
Abstract: Purpose: To evaluate the impact of image‐defined risk factor (IDRF) modification after chemotherapy on surgical outcomes, event‐free survival (EFS), and overall survival (OS) among patients enrolled in the European Unresectable Neuroblastoma (EUNB) study. Methods: IDRFs were assigned according to the corresponding surgical risk factors list reported in the database. Surgical outcomes, EFS, and OS were related to IDRF modification with chemotherapy. The predictive value of preoperative IDRF for surgical outcomes was analyzed. Cox proportional hazards models for EFS and OS, including preoperative IDRF, surgical outcomes, and other known clinical risk factors, were created. Results: Of the 160 patients enrolled in the EUNB study, 143 patients met the inclusion criteria. A total of 228 IDRF were thus collected. Following chemotherapy, 76 (33%) IDRF disappeared in 32.2% of patients, 33 (14%) new IDRF appeared in 18.8% of patients, and 49% of patients did not show any IDRF change. Complete resection/minimal residual disease (71.2%) was more frequent among children who had disappearance/numerical reduction of IDRF ( P = 0.005). Infiltration of the branches of the mesenteric artery was predictive of an unfavorable surgical outcome. Prolonged preoperative chemotherapy over five courses and encasement of the celiac axis and/or mesenteric artery origin impacted EFS and OS. Conclusions: The unchanged IDRF pattern in 50% of patients and the appearance of new IDRF during chemotherapy in approximately 20% of patients strengthens the idea that prolonged chemotherapy is useless for improving surgical resection in this population of patients. In addition, midline perivascular abdominal preoperative IDRF appeared to be predictive not only of surgical outcomes but also of EFS and OS.